Investigating the Antifungal Efficiency of Haemolymph and Aqueous Extraction of Red Velvet Mite, T. grandissimum - George, Lighty; Padmalatha, C.; Ranjitsingh, A. J. A.; Dhasarathan, P. (New Visions in Biological Science Vol. 6, 2021)
Antifungal activity of the extracts of whole red velvet mite, skin and fresh haemolymph was evaluated. It was very interesting to observe that all the above three components registered a good antifungal activity. Of the three products of mites tested, the fresh haemolymph registered the maximum antifungal activity. Next to the haemolymph, the alcohol extracts of the skin exhibited a high antifungal activity. A dose dependent variation was observed in the antifungal activity. The extracts of haemolymph at a dose level of 200 mg/disc showed the highest inhibitory activity. We have concluded red velvet mites also one of the important zoo therapeutic agent for modern medicines.